PENGARUH MEDIA SOSIAL MARKETING TERHADAP PEMBELIAN ULANG PRODUK ELSKIN BEAUTY CARE - FLORITA, ELSANITA HAPPY (FEBI IAI Al Muhammad Cepu, 2024)
This research aims to investigate and analyze the influence of social media marketing on repurchase behavior of Elskin Beauty Care products. With the increasing use of social media in product marketing, this research seeks to understand the extent to which social media interactions and content influence consumer decisions in repurchasing Elskin Beauty Care products. Thus, this research is expected to provide better insight into how social media marketing works. can influence consumer repurchase behavior towards Elskin Beauty Care products, as well as contribute to the development of more effective marketing strategies in this digital era.